Use of Interdisciplinary Integration in Learning the Genre Tuyuk - Abduganievich, Abdullaev Komilzhon (Research Parks Publishing LLC, 2021)
The article describes the role and effective methods of using interdisciplinary integration in the process of teaching the genre of chickens in secondary schools, academic lyceum literature classes based on many years of practical experience.